Lymphaticovenular anastomosis to prevent cellulitis associated with lymphoedema. Issue 11 (13th August 2014) - Mihara, M.; Hara, H.; Furniss, D.; Narushima, M.; Iida, T.; Kikuchi, K.; Ohtsu, H.; Gennaro, P.; Gabriele, G.; Murai, N.
<x xml:space="preserve">Abstract</x> Background One of the complications of lymphoedema is recurrent cellulitis. The aim was to determine whether lymphaticovenous anastomosis (LVA) was effective at reducing cellulitis in patients with lymphoedema. Methods This was a retrospective review of patients with arm/leg lymphoedema who underwent LVA. The frequency of cellulitis was compared before and after surgery. The diagnostic criteria for cellulitis were a fever of 38·5°C or higher, and warmth/redness in the affected limb(s). Results A total of 95 patients were included. The mean number of episodes of cellulitis in the year preceding surgery was 1·46, compared with 0·18 in the year after surgery (P < 0·001). Conclusion LVA reduced the rate of cellulitis in these patients with lymphoedema.